A savage war of peace : Algeria 1954-1962 - Horne, Alistair (London : Papermac, 1996)
In this book Alistair Horne tells the story of the Algerian War, which killed an estimated million Muslim Algerians, caused the fall of six French Prime Ministers and came close to bringing down de Gaulle.
Previous edition: London : Macmillan, 1977.
Includes bibliographical references (574-580) and index.
Keywords: 1945-1962; Oorlogen; Algeria -- History -- 1945-1962.; x; Algeria; History